An investigation of sponsor attributes on six megaproject cases. Issue 1 (16th November 2021) - Louw, Willem; Steyn, Herman; Wium, Jan; Gevers, Wim
Abstract : Purpose: Executive sponsors play a significant role in the success of megaprojects which, in turn, affect national economies and millions of people. However, the literature on the requisite attributes of project sponsors on megaprojects is still sparse. The purpose of the paper is to provide guidelines to company boards and executives who are tasked to appoint suitable executive sponsors to megaprojects. Thus, the paper contributes to the sparse literature on megaproject sponsors. Design/methodology/approach: A total of 26 senior managers, with experience in megaprojects ranging from 8 to 15 years – and who were involved in 6 recent megaprojects with a combined value of US13.75bn – were interviewed on the attributes of megaproject sponsors. Transcriptions of semi-structured, open-ended interviews were analysed with computer-assisted qualitative data analysis software (CAQDAS). Findings: The study identified the most essential attribute as appropriate seniority, being empowered and accountable, with appropriate seniority, being empowered and accountable, with apposite credibility and with both personal and positional power. The study also uncovered 13 attributes – all components of "competence" – which have not previously been explicitly identified in literature as elements of sponsor "competence". Originality/value: In the current study guidelines are provided for the selection and appointment of appropriate megaproject sponsors.